Minimally invasive approaches to the management of anastomotic leakage following restorative rectal cancer resection. (17th July 2019) - Creavin, B.; Ryan, É. J.; Kelly, M. E.; Moynihan, A.; Redmond, C. E.; Ahern, D.; Kennelly, R.; Hanly, A.; Martin, S. T.; O'Connell, P. R.; Brophy, D. P.; Winter, D. C.
Abstract: Aim: Management of anastomotic leakage (AL) following rectal resection has evolved with increasing use of less invasive techniques. The aim of this study was to review the management of AL following restorative rectal cancer resection in a tertiary referral centre. Method: A retrospective review of a prospectively maintained database was performed. The primary outcome was successful management of AL. The secondary outcome was the impact of AL on oncological outcome. Results: Five hundred and two restorative rectal cancer resections were performed during the study period. The incidence of AL was 9.9% ( n  = 50). AL occurred more commonly following neoadjuvant chemoradiotherapy ( n  = 31/252, 12.3%) than in those who did not receive neoadjuvant chemoradiotherapy ( n  = 19/250, 7.6%; P  = 0.107); however, this was not statistically significant. Successful minimally invasive drainage was achieved in 28 patients (56%, radiological n  = 24, surgical n  = 4). Trans‐rectal drainage was the most common drainage method ( n  = 14). The median duration of drainage was longer in the neoadjuvant group (27 vs 18 days). Surgical intervention was required in 11 patients, with anastomotic takedown and end‐colostomy formation was most commonly required. Successful management of AL with drainage (maintenance of the anastomosis without the need for further intervention) was achieved in 26 of the 28 patients. There were no significant differences in overall or disease‐free survival when patients with AL were compared with patients without AL (69.4% vs 72.6%, P  = 0.99 and 78.7% vs 71.3%, P  = 0.45, respectively). Conclusion: In selected patients, AL following restorative rectal resection can be effectively controlled using minimally invasive radiological or surgical drainage without the need for further intervention.